2001
DOI: 10.1111/j.1559-1816.2001.tb02679.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Sexual Aggression and Victimization Among Homosexual Men1

Abstract: This study examined risk factors of sexual aggression and victimization among homosexual men (N= 310). They completed the Homosexual Experiences Survey to record sexual aggression and victimization and provided information about 2 groups of potential risk factors: childhood abuse and sexual lifestyle (number of partners, age at first intercourse, age at coming out, accepting or paying of money for sex, and rape proclivity). One in 4 respondents reported severe forms of sexual victimization; 17% reported modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 44 publications
4
30
0
Order By: Relevance
“…Higher rates of CEA have also been reported among adjudicated adolescent sexual offenders (Zakireh, Ronis, & Knight, 2008) and adult sexual offenders (Lee et al, 2002) than in comparison samples of nonsexual offenders. These results have been replicated in an international sample, specifically, a community sample of German men (Krahe, Scheinberger-Olwig, & Schütze, 2001). Another study that examined a composite measure of child emotional and physical abuse among high school students also found that these experiences were directly related to SV perpetration among males (Fineran & Bolen, 2006).…”
Section: Childhood Maltreatment As a Predictor Of Sexual Violence Persupporting
confidence: 48%
“…Higher rates of CEA have also been reported among adjudicated adolescent sexual offenders (Zakireh, Ronis, & Knight, 2008) and adult sexual offenders (Lee et al, 2002) than in comparison samples of nonsexual offenders. These results have been replicated in an international sample, specifically, a community sample of German men (Krahe, Scheinberger-Olwig, & Schütze, 2001). Another study that examined a composite measure of child emotional and physical abuse among high school students also found that these experiences were directly related to SV perpetration among males (Fineran & Bolen, 2006).…”
Section: Childhood Maltreatment As a Predictor Of Sexual Violence Persupporting
confidence: 48%
“…punished, compared with homosexual men who did not report sexual aggression (Krahé, Scheinberger-Olwig, and Schütze, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Aosved, Long, and Voller (2011) found that male college students with a history of CSA were more likely to experience ASA than those without such histories. Only a few studies have examined experiences of revictimization among sexual minority populations of men, indicating that sexual minority men report similar patterns of CSA to ASA risk as heterosexual women (Coxell, 1999; Krahé, Scheinberger-Olwig, & Schütze, 2001). For example, Balsam et al (2011) found that CSA history increased the risk of experiencing rape among adult gay men, and Kalichman et al (2001) found that one third of sexual minority men in their study who experienced CSA also experienced ASA.…”
Section: Potential Risk Factors For Adult Sexual Assault Among Sexualmentioning
confidence: 99%